2021
DOI: 10.1002/adsc.202100828
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the Reactivity of the Langlois Reagent and Styrenes with Cyanoarenes Organophotocatalysts under Visible‐Light

Abstract: The selective one-step access to fluoroalkylated hexestrol derivatives, nonsteroidal estrogens, is achieved in good to excellent isolated yields under organophotoredox conditions by using the stable and easy to handle Langlois reagent.Furthermore, the challenging selective hydrotrifluoromethylation of styrenes proceeds under mild reaction conditions without the requirement for any additive. We assume that the solvent drives the reaction pathway towards either the reduction or the dimerization of the radical in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 88 publications
0
13
0
Order By: Relevance
“… [172] The conditions could be applied to the intramolecular hydro‐trifluoromethylation of benzyl‐protected homoallyl alcohol and amine derivatives ( vide infra , Scheme 187). Very recently, a similar reaction using DMSO instead of 1,4‐dioxane−MeOH as the solvent has been demonstrated by Tlili and coworkers [173] . Under these conditions, the formation of a carbanion intermediate during reductive quenching was proposed.…”
Section: Hydro‐trifluoromethylationmentioning
confidence: 74%
“… [172] The conditions could be applied to the intramolecular hydro‐trifluoromethylation of benzyl‐protected homoallyl alcohol and amine derivatives ( vide infra , Scheme 187). Very recently, a similar reaction using DMSO instead of 1,4‐dioxane−MeOH as the solvent has been demonstrated by Tlili and coworkers [173] . Under these conditions, the formation of a carbanion intermediate during reductive quenching was proposed.…”
Section: Hydro‐trifluoromethylationmentioning
confidence: 74%
“…This method afforded the products with 30-80% yields. 12 This article is protected by copyright. All rights reserved.…”
Section: Synopen Spotlightmentioning
confidence: 99%
“…This method afforded the products with 30-80% yields. 12 Liu et al developed a transition-metal-free, graphene oxide (GO) catalyzed direct C-H trifluoromethylation of alkynes and quinoxalinones with Langlois reagent that afforded the trifluoromethylated quinoxalin-2(1H)-one product under ambient atmosphere. 13 Tang et al have demonstrated the first Fe-catalyzed regioselective perfluoromethylalken-and alkynylation of 1,4-naphthoquinones using NaSO₂CF₃ and K 2 S 2 O 8 as an oxidant.…”
Section: Spotlight Synopenmentioning
confidence: 99%
“…Homo-coupling reaction of styrene derivatives mediated by the addition of CF 3 radical could also afford fluorine-substituted hexestrol, but it could only be observed by GC-MS or separated as one by-product. [9] Recently, Tlili and co-workers [10] reported a photocatalyzed strategy using R F SO 2 Na (R F =CF 3 , CF 2 H, CF 2 H) and styrenes as substrates, which successfully afforded 1,4-(CF 3 ) 2 hexestrols, as well as 1,4-(CF 2 H) 2 and 1,4-(CFH 2 ) 2 products (Scheme 1c). Method to efficiently introduce bis-difluoroacetate into the hexestrol skeletal is rarely reported, only one example obtaining diethyl 2,2, 7,7-tetrafluoro-4,5-dimethyl-4,5-diphenyloctanedienoate in 60% yield with stoichiometric copper reagent and high temperature has been reported.…”
Section: Introductionmentioning
confidence: 99%